Can an Imaging Marker of Consistency Predict Intraoperative Experience and Clinical Outcomes for Vestibular Schwannomas? A Retrospective Review - Macielak, Robert J.; Harris, Michael S.; Mattingly, Jameson K.; Shah, Varun S.; Prevedello, Luciano M.; Adunka, Oliver F. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective The main purpose of this article is to determine if vestibular schwannoma consistency as determined by tissue intensity on T2-weighted magnetic resonance imagings (MRIs) is predictive of intraoperative experience and postoperative clinical outcomes.Study Design Retrospective chart review.Setting Tertiary referral center.Patients Seventy-seven patients diagnosed with vestibular schwannomas who were treated with microsurgical resection.Intervention Diagnostic.Main Outcome Measures Intraoperative measures include totality of resection, surgical time and cranial nerve VII stimulation and postoperative measures include House–Brackmann grade and perioperative complications.Results Tumor consistency determined via tissue intensity on MRI was only found to correlate with surgical time, with a softer tumor being associated with a longer surgical time (p < 0.0001). However, this was primarily driven by tumor volume with larger tumors being associated with longer surgical time based on multivariate analysis. None of the other intraoperative or postoperative measures considered were found to correlate with tumor consistency.Conclusions Tumor consistency determined by MRI is not predictive of intraoperative experience or postoperative outcomes in vestibular schwannomas. Tumor volume is the strongest driver of these outcome measures as opposed to tumor consistency.
Keywords: vestibular schwannoma; consistency; clinical outcomes